Incorporation of batteries in reliability assessment of power systems (2025)
The integration of Battery Energy Storage Systems (BESS) was examined to assess its impact on the reliability of modern power systems. Given the fluctuations in power generation and consumer demand, BESS serves as a crucial solution for energy storage. The analysis used simulations using the IEEE Reliability Test System and DIgSILENT PowerFactory to compare scenarios with and without the incorporation of BESS. The study found that BESS significantly enhances reliability indices, improves load flow characteristics, and yields positive economic outcomes. In particular, BESS effectively mitigates transmission line congestion and reduces the impact of outages, thus playing a critical role in reinforcing power system stability.